Mapping Historical Water-Supply Qanat Based On Fuzzy Method. An Application to the Isfahan Qanat (Isfahan, Iran) - S. Behzadi; Z. Mousavi; E. Norouzi (Numerical Methods in Civil Engineering)
According to the geographical location of Iran, it enjoys both arid and semi-arid weather, which has been the cause of water shortage problems. Therefore, water has been one of strategic importance in Iran. When the population dramatically increased in ancient Iran, the demand for supplying water also increased simultaneously and brought about the need for the invention of a new way for supplying water from the ground by using gravity. This invention was named Qanat, and it has an important role for managing groundwater in arid and semi-arid areas like Isfahan. Qanat is a sustainable way for water supply in many regions. As qanat is a cultural heritage which is still prevalent in some regions of the country, it has been of great importance not only in the history of Iran but also recognized around the world as an unprecedented invention. The unparalleled source of this ancient invention and its popularity has led to their preservation in Iran and also made it famous around the world. In this article, due to the importance of its cultural heritage, attempts have been made to find the routes of the qanat in Isfahan using available spatial layers such as flood way, stream, ditch, watercourse, bush, etc. based on fuzzy logic method. To this regard, three different scenarios of fuzzy logic rules are proposed and consequently three paths are obtained for each group of fuzzy rules. Then, the explored routes are compared with the qanat route that was found by geophysics institute in Iran. The similarity of the most desirable map with the actual one was 73 percent.